The development of online textbook management system for primary school / Nor Hekmah Mohd Yasin - Mohd Yasin, Nor Hekmah (2017)
This research project is about the Development of Online Textbook Management System for Primary School. It is an inventory system to help the unit of Textbook Loan Scheme (TBLS) to manage the distribution of textbook such as keep the details of textbook and records the student details and the textbook that they received. The teachers face difficulties in managing the distribution of textbooks. There are many forms that students and teachers need to fill in. This situation can leads to human error where the detail is not consistent. It is important to develop an inventory system to manage the information regarding to the textbook systematically. Online Textbook Management System is built for Sekolah Rendah Batu 38 at Sabak Bernam, Selangor. This system will be used by TBLS units to manage textbook distribution at their school. The methodology used in the development of this project is using Web Development Life Cycle (WDLC). This project will give the significant to their users, teachers, students, parents, and the Ministry of Education. The information will be stored in database and can be access at anywhere and anytime with internet connection. The system also has tracing and tracking function. This function is used to trace the owner of textbook, availability of textbook and the condition of textbook. The system can be used at the end of the year to check the detail of textbooks and students when the students return the textbooks. For future recommendation, this system still needs an improvement and enhancement in order to provide an effective and efficient system to the user. In future the Online Textbook Management System can be enhanced by retrieved the data of student from registration system. Besides that the parents can use the system to checking the list and details of textbook that receive by their children. Implementing a mobile application that able to scanning the bar code and QR code where the information of students and textbook can be stored accurately